2017
DOI: 10.4103/aca.aca_229_16
|View full text |Cite
|
Sign up to set email alerts
|

Thyromental height test for prediction of difficult laryngoscopy in patients undergoing coronary artery bypass graft surgical procedure

Abstract: Background:Patients undergoing coronary artery bypass graft (CABG) procedures have higher incidence of difficult laryngoscopy and intubation than general surgery population. Accurate prediction of difficult laryngoscopy in CABG patients is desirable to reduce the hemodynamic response and myocardial oxygen requirements. Recently, thyromental height test (TMHT) has been proposed as one of the highly sensitive and specific bedside tests to predict difficult airway. We, in our prospective observational study, eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 14 publications
2
23
1
Order By: Relevance
“…The TMHT observations from our study are comparable to the original data from an Iranian population (314 patients), and subsequent data from an Indian population (345 patients) utilising simlar cutoffs at 50 mm. [ 1 2 ] The sensitivity (84.6%), specificity (98.9%), PPV (88%), and NPV (98.6%) of TMHT from our study is comparable to the original Iranian study that produced the coresponding values as 82.6%, 99.35, 90.45, and 98.6% respectively. [ 1 ] The high PPV (88%) along with an accuracy close to 100% (98.63%) from our data might indicate that a high proportion of difficult laryngoscopy could be predicted when the TMH is below 50 mm.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…The TMHT observations from our study are comparable to the original data from an Iranian population (314 patients), and subsequent data from an Indian population (345 patients) utilising simlar cutoffs at 50 mm. [ 1 2 ] The sensitivity (84.6%), specificity (98.9%), PPV (88%), and NPV (98.6%) of TMHT from our study is comparable to the original Iranian study that produced the coresponding values as 82.6%, 99.35, 90.45, and 98.6% respectively. [ 1 ] The high PPV (88%) along with an accuracy close to 100% (98.63%) from our data might indicate that a high proportion of difficult laryngoscopy could be predicted when the TMH is below 50 mm.…”
Section: Discussionsupporting
confidence: 74%
“…[ 3 ] The study also produced a low PPV of 20.87% and failed to show the efficacy of TMHT, as revealed by us and others. [ 1 2 ] It has to be noted, however, that their mean TMH was only 45 mm, roughly 15 mm less noted by other studies. The measurement was done in a similar head and neck position reported by other studies.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…The test is based on the height between the anterior border of the mentum and the thyroid cartilage, while the patient lies supine with the mouth closed ( Fig 2 ) [ 10 ]. Recent studies reported the TMHT to be more accurate to predict difficult intubation, compared to widely used purely anatomical measurements [ 10 , 16 ]. Clinical studies are lacking, therefore the goal of this study was to determine clinical performance and usefulness of the TMHT as a predictor of difficult intubation.…”
Section: Introductionmentioning
confidence: 99%